Lowering barometric pressure induces neuronal activation in the superior vestibular nucleus in mice - Sato, Jun; Inagaki, Hideaki; Kusui, Mayu; Yokosuka, Makoto; Ushida, Takahiro (PLOS ONE, 2019)
Weather changes accompanied by decreases in barometric pressure are suggested to trigger meteoropathy, i.e., weather-related pain. We previously reported that neuropathic pain-related behavior in rats is aggravated by lowering barometric pressure, and that this effect is abolished by inner ear lesions. These results suggest that mechanisms that increase vestibular neuronal activity may parallel those that contribute to meteoropathy generation. However, it remains unknown whether changes in barometric pressure activate vestibular neuronal activity. To address this issue, we used expression of c-Fos protein as a marker for neural activation. Male and female mice were placed in a climatic chamber, and the barometric pressure was lowered by 40 hPa, from 1013 hPa, for 50 min (LP stimulation). The total number of c-Fos-positive cells in the vestibular nuclei was counted bilaterally after LP stimulation. We also video-recorded mouse behaviors and calculated the total activity score during the LP stimulation. LP stimulation resulted in significant c-Fos expression in the superior vestibular nucleus (SuVe) of male and female mice. There was no effect of LP stimulation on the total activity score. These data show that distinct neurons in the SuVe respond to LP stimulation. Similar mechanisms may contribute to the generation of meteoropathy in humans.